Antara Destructive, Beneficial, dan Ambivalent: Membongkar Ideologi Lingkungan Khittah Perjuangan HMI MPO Melalui Analisis Wacana Eko-kritis - Anam, Haikal Fadhil (AT-THARIQ: Jurnal Studi Islam dan Budaya, 2024)
This study investigates the hidden ideologies within HMI MPO's "Khittah Perjuangan" by employing Eco-critical Discourse Analysis, a blend of Fairclough's Critical Discourse Analysis and Stibbe's ecolinguistics. The research aims to uncover how HMI MPO perceives the human-nature relationship and evaluates these perceptions through an ecological lens. Utilizing a qualitative approach, the study involves three stages: data collection, critical discourse analysis, and ecolinguistic analysis. Key findings include the portrayal of humans as "khalifah" (stewards) responsible for environmental stewardship, and the concept of "sunnatullah" (natural laws) advocating for harmony with ecological systems. However, the use of exploitative language, such as "dominating nature," indicates a potential shift towards a destructive discourse. The study reveals that while HMI MPO promotes beneficial narratives emphasizing sustainability and respect for nature, there are ambivalent elements that require careful interpretation to avoid justifying environmental exploitation. By critically assessing the ecological discourses within "Khittah Perjuangan," the research highlights the importance of aligning organizational ideologies with sustainable practices and the potential role of HMI MPO in fostering ecological awareness and action.Keywords: HMI MPO, khittah Perjuangan, ideology, human-nature, eco-critical discourse